Hubungan Pengetahuan Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja UPT Puskesmas Rumbio Jaya - Laila Silvi Hariani; Dewi Anggriani Harahap; Sri Hardianti (Excellent Health Journal, 2025)
One of the nutritional problems that occurs in pregnant women is anemia. According to the World Health Organization (WHO) in 2020, every year around 40% of pregnant women worldwide experience anemia, mainly due to iron deficiency. This anemia must be avoided by pregnant women because the impact of anemia on pregnant women themselves is miscarriage, bleeding during pregnancy, premature birth, fetal disorders, labor and postpartum disorders. The purpose of this study was to determine the relationship between maternal knowledge about nutrition and the incidence of anemia in pregnant women at the Rumbio Jaya Health Center UPT. This type of research is quantitative analytical with a cross-sectional design. The population in this study were all pregnant women in Trimester II and III in the Rumbio Jaya Health Center work area in June 2024, totaling 96 people. The sample in this study was the total population of 96 people. The data collection tool in this study used a questionnaire. This study used univariate and bivariate analysis with the chi square test. The results of the study showed that 52 respondents (54.2%) had less knowledge and 56 respondents (58.3%) experienced anemia in pregnant women. There is a relationship between knowledge and the incidence of anemia in pregnant women in the work area of ​​Rumbio Jaya Health Center UPT with a p value of 0.001. It is expected that the Health Center will further improve education, counseling and monitoring for pregnant women related to Fe tablet supplementation as an effort to prevent anemia in pregnancy.